Highly Efficient One-Step Protein Immobilization on Polymer Membranes Supported by Response Surface Methodology - Schmidt, Martin; Abdul Latif, Amira; Prager, Andrea; Gläser, Roger; Schulze, Agnes (Frontiers in Chemistry, 2022)
Immobilization of proteins by covalent coupling to polymeric materials offers numerous excellent advantages for various applications, however, it is usually limited by coupling strategies, which are often too expensive or complex. In this study, an electron-beam-based process for covalent coupling of the model protein bovine serum albumin (BSA) onto polyvinylidene fluoride (PVDF) flat sheet membranes was investigated. Immobilization can be performed in a clean, fast, and continuous mode of operation without any additional chemicals involved. Using the Design of Experiments (DoE) approach, nine process factors were investigated for their influence on graft yield and homogeneity. The parameters could be reduced to only four highly significant factors: BSA concentration, impregnation method, impregnation time, and electron beam irradiation dose. Subsequently, optimization of the process was performed using the Response Surface Methodology (RSM). A one-step method was developed, resulting in a high BSA grafting yield of 955 mg m–2 and a relative standard deviation of 3.6%. High efficiency was demonstrated by reusing the impregnation solution five times consecutively without reducing the final BSA grafting yield. Comprehensive characterization was conducted by X-ray photoelectron spectroscopy (XPS), Fourier-transform infrared spectroscopy (FTIR), and measurements of zeta potential, contact angle and surface free energy, as well as filtration performance. In addition, mechanical properties and morphology were examined using mercury porosimetry, tensile testing, and scanning electron microscopy (SEM).